1991
DOI: 10.1212/wnl.41.10.1620
|View full text |Cite
|
Sign up to set email alerts
|

Sentence comprehension and praxis deficits in Parkinson's disease

Abstract: We evaluated the ability of nondemented patients with idiopathic Parkinson's disease (PD) to interpret various aspects of sentences and to perform learned limb and oral gestures. The patients were significantly compromised in their ability to answer simple questions about sentences such as "The eagle chased the hawk that was fast. Which bird was chased?" A discriminant analysis revealed that up to 73% of PD patients differ from control subjects in their ability to perform this task. Patients with PD were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…In movement disorders a valid assessment is difficult since praxis deficits are superimposed on elementary motor dysfunctions like bradykinesia (Zadikoff and Lang 2005; Vanbellingen et al 2012). In PD, 17–64 % of the patients exhibit apraxic symptoms (Grossman et al 1991; Leiguarda et al 1997; Vanbellingen et al 2012). This variability in prevalence figures can most likely be attributed to variable apraxia assessments and patients investigated at different disease stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In movement disorders a valid assessment is difficult since praxis deficits are superimposed on elementary motor dysfunctions like bradykinesia (Zadikoff and Lang 2005; Vanbellingen et al 2012). In PD, 17–64 % of the patients exhibit apraxic symptoms (Grossman et al 1991; Leiguarda et al 1997; Vanbellingen et al 2012). This variability in prevalence figures can most likely be attributed to variable apraxia assessments and patients investigated at different disease stages.…”
Section: Introductionmentioning
confidence: 99%
“…The latter study also report that apraxic deficits do not improve with dopaminergic treatment. Importantly, apraxia scores in PD are not correlated with motor disabilities (Goldenberg et al 1986; Grossman et al 1991; Leiguarda et al 1997; Vanbellingen et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…This work showed significantly impaired processing of resource-demanding sentences that stress working memory (Grossman, et al, 1991; Grossman, et al, 1992), as well as difficulty understanding grammatically complex sentences in the setting of increased resource demands such as speeded presentation (C. Lee, et al, 2003) or concomitant performance of a secondary task (Grossman, et al, 2000). This pattern of difficulty was equally evident in an on-line study of sentence processing (Grossman, et al, 2002), emphasizing that these findings could not be easily attributed to task-related demands.…”
Section: Discussionmentioning
confidence: 92%
“…This work has demonstrated sentence processing difficulty in LBSD using a variety of techniques. In the earliest of these studies, probes of sentences varying in grammatical complexity and length revealed a significant sentence processing deficit that was attributed to working memory limitations (Grossman, et al, 1991; Grossman, Carvell, Stern, Gollomp, & Hurtig, 1992). Reduced comprehension of lengthy, grammatically complex sentences was demonstrated as resource demands increased, such as performing a secondary task concurrently (Grossman, Kalmanson, Bernhardt, Stern, & Hurtig, 2000) or increasing sentence presentation speed (C.…”
Section: Introductionmentioning
confidence: 99%
“…IMA and LKA are frequently seen in atypical parkinsonisms, such as progressive supranuclear palsy (PSP), dementia with Lewy Bodies (DLB) and as a hallmark in corticobasal degeneration (CBD) [2]. Mild IMA may even occur in some patients with Parkinson’s disease (PD) [3,4,5,6,7] and LKA may be more common than previously thought [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%